The War for Talent - Edward G. Michaels III; Beth Axelrod; Helen Handfield-Jones (Boston, MA Harvard Business School Press, 2001)
In 1997, a groundbreaking McKinsey study exposed the "war for talent" as a strategic business challenge and a critical driver of corporate performance. Then, when the dot-com bubble burst and the economy cooled, many assumed the war for talent was over. It's not. Now the authors of the original study reveal that, because of enduring economic and social forces, the war for talent will persist for the next two decades. McKinsey & Company consultants Ed Michaels, Helen Handfield-Jones, and Beth Axelrod argue that winning the war for leadership talent is about much more than frenzied recruiting tactics. It's about the timeless principles of attracting, developing, and retaining highly talented managers - applied in bold new ways. And it's about recognizing the strategic importance of human capital because of the enormous value that better talent creates.Fortified by five years of in-depth research on how companies manage leadership talent - including surveys of 13,000 executives at more than 120 companies and case studies of 27 leading companies - the authors propose a fundamentally new approach to talent management. They describe how to: create a winning EVP (employee value proposition) that will make your company uniquely attractive to talent; move beyond recruiting hype to build a long-term recruiting strategy; use job experiences, coaching, and mentoring to cultivate the potential in managers; and, strengthen your talent pool by investing in A players, developing B players, and acting decisively on C players.Central to this approach is a pervasive talent mindset - a deep conviction shared by leaders throughout the company that competitive advantage comes from having better talent at all levels. Using practical examples from companies such as GE, The Home Depot, PerkinElmer, Amgen, and Enron, the authors outline five imperatives that every leader - from CEO to unit manager - must act on to build a stronger talent pool. Written by recognized authorities on the topic, this is the definitive strategic guide on how to win the war for talent.
Keywords: Business; Leadership; Management; Nonfiction; Executive ability; Personnel management; Employee motivation; Employee retention; Global Citizenship (BIN1064-N)